A review of mathematical models of anaerobic digestion and their contributions to energy conversion of waste from the procesing of agro-food products - DEGLA, AYMARD GUY; GODJO, THIERRY; TOGBENON, Alain; OSMAN, Shaibu (My University, 2022)
The objective of this work is to take advantage of existing mathematical models of anaerobic digestion processes in order to devise a new model that will optimize the methanization of biomass waste from the processing of agro-food products in Benin. Our arguments are based, on the one hand, on principles of energy conversion processes, the application of physical-chemical laws and the law of conservation of matter, and on the other hand, on the features of existing models that yield optimal energy conversion of waste fromthe processing of agro-food products. Several mathematical models of anaerobic digestion have been identified, described and analyzed in the context of energy conversion of agro-food waste. These models differ in the number of digestion steps and/or in the digestion operating mode. The analysis shows that for some models, the biomasses used are agro-food products or waste products, while for other models no biomass is used. Moreover, when the growth rate of bacteria is an increasing positive and bounded function, we observe that the energy conversion rate is optimal shortly before half of the conversion time. For other models, the dilution rate, the substrate concentration and the volatile fatty acid concentration are the optimization parameters for energy conversion. Finally, all the models identified, described and analyzed in the context of energy conversion of agro-food waste, those of Arras and Salih are developed when the digester is in batch operation. These models differ in the digestion mode and the number of digestion steps considered.
Keywords: Mathematical Models; Anaerobic; Digestion; Waste Biomass; Energy; Conversion; Optimization.